Conclusions from the Mexican National Nutrition Survey 1999: translating results into nutrition policy Conclusiones de la Encuesta Nacional de Nutrición 1999: traduciendo resultados a política nutricional - Juan A Rivera; Jaime Sepúlveda Amor (Instituto Nacional de Salud Pública, 2003)
OBJECTIVE: This article presents and overview of the main results and conclusions from the Mexican National Nutrition Survey 1999 (NNS-1999) and the principal nutrition policy implications of the findings. MATERIAL AND METHODS: The NNS-1999 was conducted on a national probabilistic sample of almost 18 000 households, representative of the national, regional, as well as urban and rural levels in Mexico. Subjects included were children <12 years and women 12-49 years. Anthropometry, blood specimens, diet and socioeconomic information of the family were collected. RESULTS: The principal public nutrition problems are stunting in children < 5 years of age; anemia, iron and zinc deficiency, and low serum vitamin C concentrations at all ages; and vitamin A deficiency in children. Undernutrition (stunting and micronutrient deficiencies) was generally more prevalent in the lower socioeconomic groups, in rural areas, in the south and in Indigenous population. Overweight and obesity are serious public health problems in women and are already a concern in school-age children. CONCLUSIONS: A number of programs aimed at preventing undernutrition are currently in progress; several of them were designed or modified as a result of the NNS-1999 findings. Most of them have an evaluation component that will inform adjustments or modifications of their design and implementation. However, little is being done for the prevention and control of overweight and obesity and there is limited experience on effective interventions. The design and evaluation of prevention strategies for controlling obesity in the population, based on existing evidence, is urgently needed and success stories should be brought to scale quickly to maximize impact. OBJETIVO: Este artículo presenta una visión general de los resultados y conclusiones más importantes de la Encuesta Nacional de Nutrición realizada en México en 1999 (ENN-1999) y sus principales implicaciones para políticas públicas sobre nutrición. MATERIAL Y MÉTODOS: La ENN-1999 fue realizada en una muestra probabilística de cerca de 18 000 hogares, representativa de los ámbitos nacional, regional y de zonas urbanas y rurales en México. Se incluyó a niños menores de 12 años y mujeres de 12 a 49 años. Se obtuvieron mediciones antropométricas, muestras de sangre, dieta e información socioeconómica de los hogares. RESULTADOS: Los principales problemas de nutrición pública en México son baja talla en menores de 5 años; anemia, deficiencia de hierro y zinc y concentraciones séricas bajas de vitamina C en todas las edades; y deficiencia de vitamina A en niños. La desnutrición (baja talla y deficiencia de micronutrimentos) fue más prevalente en los grupos con bajo nivel socioeconómico, en zonas rurales, el sur y en población indígena. El sobrepeso y la obesidad son serios problemas de salud pública en mujeres y ya constituyen motivo de preocupación en niños de edad escolar. CONCLUSIONES: Un importante número de programas dirigidos a prevenir la desnutrición se aplican actualmente; varios de ellos fueron diseñados o modificados como resultado de los hallazgos de la ENN-1999. La mayor parte de ellos tienen un componente de evaluación que guiará ajustes y modificaciones de su diseño e implementación. Sin embargo poco se está haciendo para la prevención y control de sobrepeso y obesidad y hay experiencia limitada sobre intervenciones efectivas. Se necesita urgentemente el diseño y evaluación de estrategias para controlar la obesidad en la población, con base en evidencia existente y las acciones exitosas deben convertirse en programas de gran escala rápidamente con el propósito de maximizar su impacto.